Answer:
D
Step-by-step explanation:
Given
9 - 7x = (4x - 3)² + 5 ← expand the squared factor
9 - 7x = 16x² - 24x + 9 + 5, that is
9 - 7x = 16x² - 24x + 14 ( subtract 9 - 7x from both sides )
0 = 16x² - 17x + 5, that is
16x² - 17x + 5 = 0 ← in standard form → D
Answer:
Step-by-step explanation:
First confirm that x = 1 is one of the zeros.
f(1) = 2(1)^3 - 14(1)^2 + 38(1) - 26
f(1) = 2 - 14 + 38 - 26
f(1) = -12 + 38 = + 26
f(1) = 26 - 26
f(1) = 0
=========================
next perform a long division
x -1 || 2x^3 - 14x^2 + 38x - 26 || 2x^2 - 12x + 26
2x^3 - 2x^2
===========
-12x^2 + 28x
-12x^2 +12x
==========
26x -26
26x - 26
========
0
Now you can factor 2x^2 - 12x + 26
2(x^2 - 6x + 13)
The discriminate of the quadratic is negative. (36 - 4*1*13) = - 16
So you are going to get a complex result.
x = -(-6) +/- sqrt(-16)
=============
2
x = 3 +/- 2i
f(x) = 2*(x - 1)*(x - 3 + 2i)*(x - 3 - 2i)
The zeros are
1
3 +/- 2i
I'm guessing it 30 it says 3 times the nber of trumpet players
Y=70x
If she types at a consistent speed for 49 minutes she will have typed 3,430 words.